Comparative Research of the Results of Functional Regionalization Methods – By the Network of Commuting in Hungary - János Pénzes; Gábor Pálóczi (DETUROPE)
The paper deals with the topic of functional regionalization and demonstrates some of the possible delimitation methodologies on the basis of commuting to work dataset provided by the 2011 census in Hungary. The main objective of the study is to compare the results of the different methods on the basis of the resulted territorial divisions, their centres and hinterlands. The method of local labour systems (LLS), the method of labour market areas (LMA) – called as EURO method – and the CURDS measure are introduced, applied and compared. The results of the calculations clearly demonstrate the different characters of the methods. The results of the LLS method are characterized by major disparities with an extremely extended Budapest LLS district. The EURO method results in a less extending central region around Budapest, however, the CURDS measure causes the most moderate inequalities among the functional regions with the smallest number of units. The differing character of the methods can be discovered in the centres as well. LLS centres indicate the polarizing character of the method preferring the largest centres, at the same time it gives possibility to the smaller centres to be delimited. The centres of the EURO method appear with the largest frequency and it gives the possibility that those centres are located in the surroundings of dominant centres. The CURDS measure is the ‘strictest’ one from this respect. The comparative results drew the attention to the differing character of centres in each part of Hungary.